A critical review of post-pandemic ELT intersections: Language, identity, and sustainability - Jenny Ngo (Universitas Muhammadiyah Malang, 2025)
The intricate relationship between language and identity holds profound implications for English Language Teaching (ELT), particularly in light of recent global transformations. This critical review systematically synthesizes literature from 2020 to 2025 to examine how identities are constructed, negotiated, and performed by key ELT stakeholders—teachers, learners, curriculum, and media—and how these dynamics intersect with the growing imperative of sustainability education. Focusing on the post-COVID-19 period, the review highlights accelerated shifts in pedagogical practices and research priorities. Drawing on sociolinguistic and poststructuralist theories, this paper critically examines the multifaceted ways in which English, as a global language, interacts with the diverse linguistic and cultural identities of those involved in its teaching and learning within this new landscape. The review employs a systematic methodology, including comprehensive database searches, rigorous study selection, and thematic data synthesis to identify key trends, persistent challenges such as native-speakerism and greenwashing, and innovative pedagogical implications shaped by this transformative period emerging from this transformative era. It argues that a critical awareness of these evolving identity dynamics, paired with the explicit integration of sustainability principles, is essential for fostering inclusive, equitable, and future-oriented ELT practices. The discussion outlines practical implications for pedagogy, including strategies that validate learner identities, promote intercultural competence, challenge linguistic hegemonies, and cultivate global citizenship and environmental responsibility. Ultimately, this paper advocates for a transformative paradigm shift in ELT that transcends a purely instrumental view of language learning to embrace its role in shaping identities and fostering the ecological consciousness required for a sustainable future.